Acceptability and effectiveness of the "family care plan" as a nutrition education approach among low income mothers in Purok Magnolia, Barangay Tunasan, Muntinlupa, Metro Manila - Ignacio, Ma. Socorro E.
This study was conducted to assess the acceptability of the Family Care Plan (FCP) in producing a change in nutrition knowledge, attitudes and practices and whether this changes was reflected in the nutritional status of the children. Likewise, the effects of some family characteristics such as age, educational attainment, occupation of parents and total monthly income in terms of responses to the FCP were determined statistically in relation to the NKAP score, diet rating and percent standard weight for age of children 1-6 years of age. The experimental and control subjects composed of mothers and preschool children totalled 46 and 56 respectively and were both from an urban low-income barangay in Muntinlupa, Metro Manila. A 20-item questionnaire was used to measure the NKAP level of the mothers, while the 24 hour food recall was used to record food intake of the preschool children. To determine the nutritional status of the children, the weight for age data were utilized. 6 months later, the same data were collected and anlyzed.The results showed that the FCP approach was effective in improving the NKAP level of mothers. It was most effective among the younger women who were less informed on nutrition and with high educational attainment. In terms of improving the quality of diets prepared, the FCP approach seemed to be most effective among women who were 25-34 years of age, who had only elementary education, were not employed and had better total family incomes. It was however noted in this study that improved NKAP did not result in improved quality of diets of the children and consequently in their weights as percent standard weight for age. On the other hand, improved diets were positively and significantly correlated with percent standard weight for age of the children. These conclusions suggest that nutrition improvement programs should always have an income improvement component to be targetted to unemployed housewives. As much as possible such an activity should not take the mothers away from home because children of women who stay home were found to be better nourished. Although the better educated groups responded less to the FCP in terms of improvement in the parameters measured, they generally had better diet rating and percent standard weight for age before the FCP and maintained this advantage 6 months later. This only indicates the importance of education in alleviating malnutrition and therefore, the poor should have better access to educational opportunities.